2022
DOI: 10.1111/jcmm.17566
|View full text |Cite
|
Sign up to set email alerts
|

A miR‐15a related polymorphism affects NSCLC prognosis via altering ERCC1 repair to platinum‐based chemotherapy

Abstract: Platinum-based chemotherapy is regarded as a preferential curative-intent option for non-small cell lung cancer (NSCLC), while the acquired drug resistance has become a major obstacle that limits its clinical application. Since the repair efficiency of tumour cells to platinum-DNA adducts plays a crucial role in chemotherapy resistance, we aimed to explore whether several meaningful polymorphisms of DNA repair genes were associated with the benefits of platinum-based chemotherapy in NSCLC patients. Firstly, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…In addition, Yu et al predicted the ERCC1 mRNA secondary structure between two genotypes of rs3212986 by bioinformatics software and found that ERCC1 rs3212986 genetic variation may affect DNA repair capacity by altering the folded stem-loop structure consisting of six repeats of “GCT”, which could impact the 18-base sequence in the 3′-UTR of ERCC1 ( 25 ). Furthermore, ERCC1 mRNA expression may be regulated by miRNAs, which could also be affected by the rs3212986 polymorphism in the target complementary sequence ( 16 , 26 ). There were some candidate miRNAs in the ERCC1 3′-UTR region identified by online websites (miRNASNP-v3, miRBase, and TargetScan Release 7.2), including 4 miRNAs of target gain (hsa-miR-3185, hsa-miR-7-5p, hsa-miR-10522-5p, and hsa-miR-6077) and 2 miRNAs of target loss (hsa-miR-6828-5p and hsa-miR-671-5p) in 3'-UTR of ERCC1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Yu et al predicted the ERCC1 mRNA secondary structure between two genotypes of rs3212986 by bioinformatics software and found that ERCC1 rs3212986 genetic variation may affect DNA repair capacity by altering the folded stem-loop structure consisting of six repeats of “GCT”, which could impact the 18-base sequence in the 3′-UTR of ERCC1 ( 25 ). Furthermore, ERCC1 mRNA expression may be regulated by miRNAs, which could also be affected by the rs3212986 polymorphism in the target complementary sequence ( 16 , 26 ). There were some candidate miRNAs in the ERCC1 3′-UTR region identified by online websites (miRNASNP-v3, miRBase, and TargetScan Release 7.2), including 4 miRNAs of target gain (hsa-miR-3185, hsa-miR-7-5p, hsa-miR-10522-5p, and hsa-miR-6077) and 2 miRNAs of target loss (hsa-miR-6828-5p and hsa-miR-671-5p) in 3'-UTR of ERCC1 .…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that A allele of the ERCC1 rs3212986 polymorphism might be a risk factor for ischemic stroke. The ERCC1 rs3212986 polymorphism, located on the 3'-UTR of the ERCC1 gene, has been widely studied in previous studies (16,22,23) and might be involved in the potential pathophysiological mechanism in ischemic stroke. ERCC1 rs3212986 polymorphism might affect the DNA repair capacity and interfere with the NER pathway by regulating ERCC1 transcription and translation and/or altering ERCC1 biological activity (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation